Typology of Poverty and Its Implications for Poverty Reduction Policies - Agussalim Agussalim (EcceS (Economics, Social, and Development Studies), 2022)
The purpose of this study is to identify conditions, characteristics, access, social environment, and opportunities that can be utilized by the poor based on regional typology in Gorontalo Province. From the results of this study, it is hoped that various policies can be formulated to help the poor get out of the poverty trap. Poverty research based on analysis of three regional typologies, namely urban, rural and coastal areas, has never been done before in Gorontalo Province. The method used in this study is descriptive-qualitative method. The types of data used are primary data and secondary data. The study will be carried out in three regional typologies, namely urban, rural and coastal areas, according to the regional characteristics of the Gorontalo Province. The location sampling technique was carried out by taking area samples in stages (multistage area sampling) to determine the research location villages. The population in this study is all poor households living in the six selected sub-districts/villages. Sampling in the six sub-districts/villages surveyed was carried out using a simple random sampling technique. The results of the study show that in general, household vulnerability to poverty seems to be associated with regional aspects, where households living in rural areas have a higher vulnerability than households in urban and coastal areas. From the survey results in three regional typologies (urban, rural, and coastal) in Gorontalo Province, it can be generally concluded that income poverty and non-income poverty are more dominant in poor households in rural areas compared to urban and coastal areas. In other words, those who live in rural areas live in poorer conditions than those who live in urban and coastal areas. From a policy perspective, this means that efforts to reduce poverty in rural areas will be relatively more difficult than the other two regions. The implication of this research is that efforts to reduce poverty in a sustainable manner need to focus more on aspects of improving the quality of human resources for poor households in all regional typologies. The government needs to design various programs that aim to: (i) reduce the number of illiterate poor people and improve their skills; (ii) increasing access of the poor to public services (especially education and health) and economic resources (especially business capital); and (iii) intensifying programs to empower the poor, through the provision of micro credit, assistance with business equipment, work-intensive programs, and others.